Dose-dependent Anti-inflammatory Effect of Silymarin in Experimental Animal Model of Acute Inflammation - Kasim M. Juma'a; Saad A. Hussain; Intesar T. Numan; Assad H. Siqar (College of Pharmacy University of Baghdad, 2017)
Silymarin, a flavolignans from seeds of â€˜milk thistleâ€™ â€œSilybum marianumâ€ has been widely used from ancient times because of its excellent hepatoprotective action. It has been used clinically to treat liver disorders including acute and chronic viral hepatitis, toxin/drug-induced hepatitis and cirrhosis and alcoholic liver disease. The efficacy and dose-response effect of silymarin (125, 250 and 500 mg/kg) were assessed using egg albumin-induced paw edema in rats as a model of acute inflammation. In this model, 56 rats were used and allocated into 7 subgroups each containing 8 rats. All treatments were given intraperitonealy 30 minutes before induction of inflammation by egg albumin and then the increase in paw edema was measured 1h, 2h and 3h after induction of inflammation by using the vernier caliper. The results indicated that silymarin, at doses range used, significantly lowered paw edema (P<0.05) an effect comparable to that produced by the reference drugs, acetyl salicylic acid, meloxicam and dexamethazone. Paw edema suppressive effect of silymarin 250 and 500 mg/kg was comparable and both of them were significantly different from that of silymarin 125 mg/kg (P<0.05). Therefore, silymarin exert an important anti-inflammatory activity in animal model of acute inflammation, which was significantly increased as the dose increased up to 250 mg/kg. Key words: Silymarin, acute inflammation, dose-response